The Effect of Concentration Index on the Profitability of the Banking System of the Member Countries of the Organization Of Islamic Cooperation - Marzieh Rafiean Esfahani; saeed Daei Karimzadeh; mahshid shaahchera; Sara Ghobadi (پژوهشهای اقتصادی, 2023)
Aim and Introduction Over the past two decades, the banking system around the world has undergone significant changes in its operating environment, and several internal and external factors have influenced its structure and performance. Despite all these changes, the banking system remains the main source of financing economic activities in many countries. Therefore, evaluating the performance of the banking system is important. Profitability is one of the influential factors in evaluating the performance of banks. Thus, it is necessary to know the effective internal and external factors. The main purpose of this paper is to evaluate the impact of the concentration index on the profitability of the banking industry. On the other hand, banks as established and organized institutions play an important role in attracting stagnant capital and transferring it to productive sectors, as well as meeting the needs of investors. Since a competitive environment in the banking system can increase efficiency and facilitate financial transactions, identifying the market structure of the banking industry is important for policymakers and banking operators, because it can be the way to remove the obstacles in creating a competitive market. The policy makers could be selected the polices that achevied the economic goles. Methodology In order to achieve this goal, the impact of factors affecting the risk and profitability of banks, we especially use the concentration index as one of the dimensions of the market structure in the banking industry. The method of estimation is generalized method of moments (GMM). For this purpose, concentration in the banking industry has been measured using the Herfindahl-Hirschman index. In addition, six control variables including capital adequacy, central bank assets ratio, deposit ratio, liquid assets ratio, credit ratio and cost-to-income ratio have been selected as explanatory-control variables. In this way, the explanatory variables of banks' profitability include bank-specific factors. Return on total assets and bank stability index have been used as profitability and risk criteria of banks. Also, the situation of the organized monetary market of 52 countries of the Organization of Islamic Cooperation was studied over the period 2005-2019. Findings Based on the findings of the research, the effects of independent variables in the profitability model are statistically significant and have positive effects on the profitability of banks. Regarding the main hypothesis of the research, i.e. the effect of the concentration index on the profitability of the banking system, it can be seen that the increase in market concentration has increased the profitability, which has a significant coefficient of 0.003817, which confirms the Structure-Conduct-Performance(SCP) hypothesis. In other words, based on this hypothesis, as the degree of market competition decreases, it becomes possible to earn higher profits. In addition, independent variables with lag of time (banking stability index, capital adequacy and return on assets) and the ratio of loans to deposits and the ratio of central bank assets have positive and significant impacts on risk. Discussion and Conclusion Experimental results have shown that the each of the independent variables has positive and significant effect on risk and profitability. The estimation results have shown the positive effect of the market concentration index on banks' profitability. In this way, in the periods when the concentration in the banking industry is higher, the profitability of the banks is high and with the increase in the level of concentration, the profitability of the banks has increased. As stated in the theoretical foundations, there are various theories regarding the relationship between concentration and profitability of banks. Although these theories differ on how to create this relationship, almost all of them emphasize that increasing concentration increases the profitability of banks and reduces competition. In other words, these theories predict that the relationship between concentration and profitability is positive. The result of fitting the research model shows a positive and significant effect of the concentration index on the return on total assets. This means that increasing market concentration has increased profitability. According to the obvious realities in the economies of the sample countries, the intensity of concentration in the banking industry have significant consequences for the profitability of banks by affecting the efficiency and effectiveness of resources. Keywords: Banking System, Profitability, Risk Management, Concentration Index JEL Classification: G21, G32, G38